A general regularized gradient-projection method for solving equilibrium and constrained convex minimization problems. (1st November 2016) - Tian, Ming; Jiao, Si-Wen
Abstract : In this article, we provide a general iterative method for solving an equilibrium and a constrained convex minimization problem. By using the idea of regularized gradient-projection algorithm (RGPA), we find a common element, which is also a solution of a variational inequality problem. Then the strong convergence theorems are obtained under suitable conditions.